The Atlantic Provinces (Benjamin New Co., Ltd.)
The Atlantic Provinces - Nova Scotia, New Brunswick, Prince Edward Island and Newfoundland have joined forces in a display of the special qualities and character of Atlantic Canada. The pavilion is located next to the Canada Pavilion on Ile Notre-Dame